Representation with/out Representation: Saudia Arabia as a Hidden Face of Globalization - Lohlker, Rüdiger (Interdisciplinary journal for religion and transformation in contemporary society, 2018)
The article discusses the European/North American concept of representation. It offers an alternative approach including the non-Western world. The case study discussed is the Kingdom of Saudi-Arabia and Wahhabism/Salafism.